Equation-Based Object-Oriented modelling and simulation of large-scale Smart Grids with Modelica. Issue 1 (July 2017) - Casella, Francesco; Bartolini, Andrea Giorgio; Leva, Alberto
Abstract: The design, control, and management of large-scale Smart Grids poses a number of challenging problems. Successfully addressing them requires high-level, flexible, efficient and scalable dynamic modelling and simulation frameworks. In this paper, the requirements for such frameworks are first stated. Then, it is shown how the equation-based, object-oriented modelling approach and the Modelica modelling language can fit those requirements.